Soil and Drought Basic Processes - Lal, Rattan (Advances in Soil Science, 2024)
Drought, a serious global issue, is being aggravated by climate change. Both pedological and agronomic droughts are a major risk factor with adverse effects on agronomic productivity, food and nutritional security, and human wellbeing.